Reformas al código orgánico integral penal (coip), a fin de sancionar a los servidores públicos, por acciones u omisiones en el control de las unidades socioeconómicas populares - Ordóñez Cabrera, Mauricio Fernando (2016)
This thesis on the problems, to guarantee the rights of citizens within the public administration, socio-economic control units, to the actions or omissions of public servants who exercise control. The punitive social control exercised by the actions of the Code Integral, sanctions offenses against the Public Administration. In the penal system, it is necessary that the rights of individuals are guaranteed, observing the due process established in Art. 76 of the Constitution of the Republic of Ecuador, the same one that guarantees the principle of legality, criminality of the acts, that infringe the legal rights that our State guarantees for citizens in a society governed by the rule of law. One of the actions or omissions, which are given by officials exercising control, is the lack of action evaluation and systematic monitoring in which the mechanisms of prevention and intervention is exercised by the state, creating legal certainty for the benefit of people in general and especially of people who in good faith put their different resources in these economic units. It is important that the system of procedural legality, allow the sanction of the acts or omissions of officials or public servants exercising control units socioeconomic popular and solidarity economy. The law has a preventive nature, and sanction for the unlawful acts.